GAINING PURCHASE INTENTION BY ELECTRONIC WORD OF MOUTH AND BRAND AMBASSADOR - Pidada, Ida Ayu Iswari; Supartyani, Ni Wayan (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: This study examines the effectiveness of e-WOM and brand ambassador toward purchase intention of Sasa product through the promotion of "Jejak Rasa” web series. The number of millennials, especially in Bali, is a driving factor for the rapid development of digital technology. Almost half of Indonesia's population has implemented the marketing process with digital marketing in their daily lives. Methods: This study will focus more on electronic word of mouth and brand ambassadors who are used as intermediaries in making purchase intentions of a product. PT. Sasa Inti will be used as an object in this study because the marketing strategy it uses has innovations that seek to continue to grow. In a customer-oriented business industry, creative and innovative marketing processes are very influential in attracting buyers' intentions. Data collection was using accidental sampling technique and tested using multiple linear regression analysis. Results: Results show electronic word of mouth has a significant positive effect on purchase intention, the brand ambassador has a significant positive effect on purchase intention, also the electronic word of mouth and brand ambassadors together have a significant effect on purchase intentions. Conclusion and suggestion: Therefore, the study was conducted to provide readers with the understanding of the effect of electronic word of mouth, brand ambassador and purchase intention in Bali. For practitioners, this research is useful in finding out the things that build purchase intention as measured by electronic word of mouth and brand ambassador in PT. Sasa Inti. Thus, other companies can develop their marketing strategy based of the result of this study.